Bearing the Stigma of HIV: Experiences and Coping Strategies in Southwest China - Yeon Jung Yu, Xiaoming Li, Shan Qiao and Yuejiao Zhou (World Health & Population, 2018)
Even as the number of people living with HIV (PLWH) is rapidly increasing in China, qualitative studies investigating the effect of HIV stigma on daily lives remain limited. The current study aims to fill this gap in research with attention to not only the experiences but also the coping strategies of PLWH in southwest China. We conducted 90 in-depth interviews in Guangxi, China. Our participants included both PLWH and individuals in their surrounding community (e.g., spouse,  children, health workers). Our interview data showed an intense manifestation of HIV stigma in domestic spheres. Other close community members (e.g., relatives, friends, neighbours) also worked both to discriminate against PLWH and simultaneously thwart possible stigma by association. By explaining how stigma affects both PLWH and their family members, the current study seeks to help both citizens and health practitioners better understand the effects of stigma on PLWH, their friends and their families.
Keywords: people living with HIV, HIV stigma, healthcare in China, coping with HIV